Educational Resource Allocation and Practices of Public Elementary School Teachers in the Implementation of the Reading Program - Glyziel Ladion; Josephine B. Baguio (Archives of Current Research International, 2025)
This study aimed to examine the relationship between educational resource allocation and the teaching practices of public elementary school teachers in implementing the school reading program. A descriptive-correlational research design was used, involving 132 public elementary school teachers in the Malalag District, Division of Davao del Sur. Data were gathered using standardized questionnaires and analyzed using mean, standard deviation, Pearson product-moment correlation, and multiple linear regression. Results showed that both educational resource allocation and teaching practices were rated as very high in implementation. A significant positive relationship was found between resource allocation and teachers’ practices, suggesting that increased allocation contributes to more effective implementation of reading programs. Among the resource domains, international trends emerged as the strongest predictor of teaching practices. In this context, “practices” refer to teachers’ strategies, activities, and approaches used in delivering reading instruction. This study contributes to the understanding of how targeted resource investment can enhance teaching effectiveness. It highlights the importance of strategic resource planning, including professional development, adoption of international best practices, and improved access to instructional materials. These findings offer practical insights for school administrators and policymakers aiming to strengthen literacy outcomes through improved support for reading programs.